Intrinsic fragment spins generated in the reactions of 20Ne with 197Au and 238U at 12.6 MeV/nucleon - Morrissey, D. J. (1982)
Fil: Morrissey, D. J. National Superconducting Cyclotron Laboratory, Michigan State University; Estados Unidos